Pitting Corrosion in AA7075 Friction Stir Welds on Minor Additions of Silver - Kodamasimham Sri Ram Vikas; Venkata Ramana Vuppala Sesha Narasimha; Koona Bhavani; Challa Kishore Reddy; Vadapalli Srinivas (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
AA7075 is extensively used in aerospace, defense, automotive applications because of its high strength to weight ratio. Issues related to fusion welding and corrosion resistance are key problems associated with these alloys. Friction stir welding is an alternative welding technique that overcomes problems associated with fusion welding. In the present investigation, preliminary studies were done on pitting corrosion behavior of AA7075 friction stir welds by adding silver along the weld joint line. Silver paste was applied along the longitudinal direction of AA7075-T6 rolled plates of 6-mm thickness and cured at 130 °C for 30 seconds. Weld joints were prepared at two different tools rotational speeds, i.e., 750 rpm and 1000 rpm, while keeping other parameters fixed. Welded joints were cut as per the required sizes to study the hardness, microstructure, and pitting corrosion resistance in various regions. It was observed that the hardness was not much affected, but pitting corrosion resistance substantially improved by trace addition of silver. In the stir zone and the thermo-mechanically affected zone, onion ring type marks were observed. Grain refinement in the stirred zone (SZ) was higher at 750 rpm compared to 1000 rpm. The increased hardness in the welds was due to grain refinement. All the observed results were correlated with microstructural features as evidenced by optical microscopy.